THE CORRELATION BETWEEN AUDIO VISUAL ON BLOOD CIRCULATION MATERIAL AND LEARNING OUTCOMES OF PRIMARY STUDENTS IN MI MUHAMMADIYAH KALIKAJAR WONOSOBO - Risqi Fani Angraeni; Ahwy Oktradiksa; Muis Sad Iman (Al-Bidayah : jurnal pendidikan dasar Islam, 2020)
The use of audio-visual media is on learning outcomes of science on circulatory material at MI Muhammadiyah Kalikajar Wonosobo. This research is a quantitative study with audio-visual media variables and variable learning outcomes of science in the blood circulation material. The population in this study was totaling 212 students. The sample in this study was 20 students. Collecting data used questionnaires, interviews, and documentation. Data analysis used product-moment correlation analysis. The results that the learning process of natural blood circulation material before using audio-visual media is less effective, the use of audio-visual media at this time in the high class is shown from the respondent's answered 55%. Improved learning outcomes of the science of blood circulation material the Minimum completeness criteria (KKM) complete predicate as many as 16 students with a percentage of 80%, and four students had not completed the KKM with a percentage of 20%. The research finding obtained rxy count value of 0.489 with a significant level of 5% higher than r table, which means Ha was accepted Ho was rejected, namely, there was a correlation between the use of audio-visual media on studying of blood circulation science materials